The intention to use of natural gas by small-medium enterprises in Sabah: lesson to tourism industry - Stephen Laison Sondoh Jr.; Julian Paul Sidin; Hassan Mudin; Geoffrey Harvey Tanakinjal (Universiti Malaysia Sabah, 2014)
This study aims to investigate the relationship between Natural Gas (NG) product attributes and intention to use NG by Small Medium Enterprises (SMEs) in Kota Kinabalu. Data from 213 SMEs senior staff and management level were used for the statistical data analysis. The multiple regression analysis results indicated that three dimensions of NG attributes namely; environmental friendly, reliability, and price had significant influence on intention to use NG. Conversely, the remaining three of the dimensions of NG attributes i.e., price value for money, production efficient and safety had no significant influence on intention to use NG. This study concluded that there were three key factors contributing SMEs intention to use NG in Kota Kinabalu, Sabah. The SMEs are more likely to use NG due to environmental friendly, followed by reliability and price. By knowing these key factors, it provides guidance for marketers to develop business strategies to attract SMEs in Kota Kinabalu to use NG as an energy option in the future.